2017
DOI: 10.3847/1538-4357/aa5d14
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Enormous Lyα Nebula in a Massive Galaxy Overdensity at z = 2.3

Abstract: Enormous Lyα Nebulae (ELANe), unique tracers of galaxy density peaks, are predicted to lie at the nodes and intersections of cosmic filamentary structures. Previous successful searches for ELANe have focused on wide-field narrowband surveys, or have targeted known sources such as ultraluminous quasi-stellar-objects (QSOs) or radio galaxies. Utilizing groups of coherently strong Lyα absorptions (CoSLAs), we have developed a new method to identify high-redshift galaxy overdensities and have identified an extreme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
169
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(182 citation statements)
references
References 87 publications
12
169
0
1
Order By: Relevance
“…At z ∼ 2 − 3, luminous LAEs are known to have counterparts in multiwavelength data (e.g., X-ray and radio) and/or extended Lyα haloes (e.g., Steidel et al 2000;Ouchi et al 2008;Cantalupo et al 2014;Cai et al 2017). A recent study, for example, has confirmed that there are excesses found in Lyα LFs at log L(Lyα) [erg s…”
Section: Introductionmentioning
confidence: 72%
“…At z ∼ 2 − 3, luminous LAEs are known to have counterparts in multiwavelength data (e.g., X-ray and radio) and/or extended Lyα haloes (e.g., Steidel et al 2000;Ouchi et al 2008;Cantalupo et al 2014;Cai et al 2017). A recent study, for example, has confirmed that there are excesses found in Lyα LFs at log L(Lyα) [erg s…”
Section: Introductionmentioning
confidence: 72%
“…The center of the MAMMOTH-I Nebula was classified by Cai et al (2017b) as 'source B'. 1 We adopt their terminology, and associate region B with the central group of galaxies, which is surrounded by diffuse light in the HST imaging.…”
Section: The Central Group (B)mentioning
confidence: 99%
“…In this paper, we present observations of extended molecular gas across a radio-quiet ELAN, namely the MAMMOTH-I Nebula at z = 2.3. The MAMMOTH-I Nebula is one of the most extreme ELANe found to date, with Lyα emission stretching across ∼440 kpc (Cai et al 2017b). It is located in the extreme galaxy overdensity BOSS1441, which traces a proto-cluster (Cai et al 2017a;Arrigoni Battaia et al 2018b;Mukae et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Warren & Møller 1996;Weatherley et al 2005;Cucciati et al 2014;Fumagalli et al 2016a;Bielby et al 2016;Péroux et al 2017;Cai et al 2017). However, due to the difficulty in mapping neutral hydrogen in emission at high redshift, until recently it has proven challenging to study in detail the connection between gas and galaxies inside overdensities beyond z 2.…”
Section: Introductionmentioning
confidence: 99%